2012
DOI: 10.1177/1359105311430004
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health: The role of neighbourhoods, psychological factors and health behaviours in predicting health outcomes for the urban poor in India

Abstract: The aim of this study was to investigate the role of neighbourhoods, psychological characteristics and health behaviours on actual health outcomes and perceived health for a lower income urban Indian sample. A cross-sectional design was used with a community sample of 491 adults in two neighbourhoods. Neighbourhood and perceived stress played a role in predicitng risk of chronic conditions as well as perceived health. Positive emotional style was associated with decreased perception of poor health. Results sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…While comorbidities are known risk factors for falls,21 the theme relating to mental stress was unexpected. This finding fits with a holistic model of health and is supported by one other research in India, which has found that perceived stress is predictive of chronic conditions and health outcomes 22. The findings of quantitative studies from India also support the perceptions of participants in the present study: falls being multifactorial and related to chronic conditions 23…”
Section: Discussionsupporting
confidence: 90%
“…While comorbidities are known risk factors for falls,21 the theme relating to mental stress was unexpected. This finding fits with a holistic model of health and is supported by one other research in India, which has found that perceived stress is predictive of chronic conditions and health outcomes 22. The findings of quantitative studies from India also support the perceptions of participants in the present study: falls being multifactorial and related to chronic conditions 23…”
Section: Discussionsupporting
confidence: 90%
“…The rapidly improving socioeconomic status in India is associated with an increased NCD risk. This may be due to a reduction of physical activity and increased rates of obesity and diabetes [4,8,9]. Diabetes Mellitus increases along a positive social gradient, with a higher prevalence in the more affluent and better educated sections of the Indian population [10].…”
Section: Introductionmentioning
confidence: 99%
“…These transformations have a potential impact on wellbeing because they alter several of the psychosocial and psychological determinants of health (Kulkarni, 2012), such as social support, attachment, and identity, and could even interact with genetic conditions (Luyten & Blatt, 2013).…”
Section: Transformation Of Communities and Health: The Case Of Depresmentioning
confidence: 99%
“…Following this idea, some empirical studies and conceptual analyses have attempted to find a connection between the transformation of communities inherent to the individualization process and the health problems that are becoming increasingly common around the world (Gotlib & Hammen, 2002), one of which is depression. The decline of traditional communities is pointed out as the cause of these problems because it alters several of the psychosocial determinants of health (Kulkarni, 2012).…”
Section: Transformation Of Communities and Health: The Case Of Depresmentioning
confidence: 99%